Valuation of a UNESCO World Heritage site Barangay Tacas and Barangay Hibao-an Sur's non use values for the church of Sto. Tomas de Villanova. - Domingo, Nasser Ray D.
This study assesses the willingness to pay (WTP) in two barangays in Iloilo city, Philippines to contribute for the conservation, preservation, and restoration of a United Nations Educational, Scientific and Cultural Organization (UNESCO) world heritage site the Sto. Tomas de Villanova church more commonly known as the Miag-ao church. The research was carried out to assess the awareness and attitude of the people towards the subject of conservation of cultural heritage sites, more specifically, the church of Santo Tomas de Villanova in Miagao, Iloilo; assess socio economic factors affecting the willingness to pay for the conservation and management of Sto Tomas de Villanova church; determine and provide a valuation of the non-use values of the Church of Santo Tomas de Villanova, as well as; provide policy implications to help raise funds for the preservation of the church., Contingent valuation method (CVM) was used to find out how much people in Brgy. Tacas, and Brgy. Hibao-an Sur, Mandurriao in Iloilo city, Phils. would be willing to pay as a one-time contribution to a conservation and preservation trust fund to be handed jointly by the Catholic Bishops' Conference of the Philippines (CBCP) and the national Historical Institute (NHI). The fund will be used for the preservation and conservation of Miagao church. The church of Santo Tomas de Villanova, built in the 18th century, withstood occasional attacks from Muslims coming from south. With its watchtowers, thick walls and secret passages to defend the town and its people, the church was dubbed as "the Miagao fortress church." With its own interpretation of European baroque architecture, the church was dubbed as one of the UNESCO world heritage sites in 1993. The report finds that 37.5 percent of the total respondents would be willing to pay a one-time contribution to support the conservation and preservation of Miagao church. It finds the most of that respondents are willing to pay because they think that it is important to preserve the heritage site for future generations. Five different bid prices were used, and was found that as the bid prices increases, the WTP decreases. There were also other factors that affect the people's willingness to pay - these include age, sex, number of years in school, number of dependents, personal and household incomes. Given results, the study also proposes and options and policy implications to improve awareness as possible revenues for the purpose of conservation and preservation of the church.